Rotational Diffusion of the α(2a) Adrenergic Receptor Revealed by FlAsH Labeling in Living Cells - Spille, Jan-Hendrik (The Biophysical Society, 2011)
The fluorescein arsenical hairpin binder (FlAsH) shows much promise to determine the relative orientations of protein regions and structures even in living cells and in the plasma membrane. In this study, we characterized FlAsH's photophysical properties by steady-state anisotropy and time-resolved single photon counting for further applications with G-protein coupled receptors. We find that FlAsH has a relatively high initial anisotropy of 0.31 ± 0.01 and a three-component fluorescence lifetime with an average of 4.1 ± 0.1 ns. We characterized the FlAsH fluorophore orientation in the α(2A) adrenergic receptor revealing rigid orientations of FlAsH in the membrane plane for rotational correlation times of ∼50 ns in living cells. To elucidate the fluorophore-membrane orientation and rotational correlation time, an anisotropy treatment similar to that of another researcher (Axelrod, D. 1979. Biophys. J. 26:557–573) was developed. The rotational correlation times were observed to increase by up to 16 ns after agonist addition. The rotational correlation time also allowed for a comparison to the theoretical relationship between translational and rotational diffusion (originally proposed by Saffman, P. G., and M. Delbrück. 1975. Proc. Natl. Acad. Sci. USA. 72:3111–3113) and revealed a discrepancy of a factor between 10 and 100.